Meningkatkan Kinerja Kerja Pada Bisnis Desimal Coffee - Dimas Mausul Haqiki; Ahmad Malik Fajar; Dwi Epty Hidayaty (Yayasan Daarul Huda Kruengmane, 2023)
Small, Micro and Medium Enterprises (MSMEs) are businesses that are much loved by Indonesian people. Starting from businesses in the trade, service, to manufacturing sectors. However, many are involved in this MSME business but their lack of ability to manage their business makes it a big enough problem for the continuity of the business in the future. The purpose of this research is to find out the importance of developing employees which will have an impact on employee performance. This study uses a descriptive method supported by the results of observations that have been obtained. This study also describes the development of employee performance in the Decimal Coffee business. Based on the results obtained, it can be seen that development can make employee work performance even better. One of the efforts to develop employee performance is by holding training programs for employees. So, work performance has an important role for the continuation of the Decimal Coffee business, good work performance can result in improvement and future business development, both short and long term. Good work performance will also affect consumer interest in the products produced, therefore training will be very useful to make consumers feel satisfied with products produced by good employee performance.